STRATEGI KEPALA MADRASAH DALAM MENGELOLA KONFLIK DI MA ANNURIYYAH - Daniatul Qoyyimah; Alisa Qutrun Nada; Umar Mansyur (Al Fuadiy Jurnal Hukum Keluarga Islam, 2022)
Conflict is a form of natural disagreement that occurs between individuals and groups because they have different attitudes, beliefs, values, and needs. Conflict should not always be interpreted as a destroyer or an attempt to destroy an educational institution. The existence of conflict in an educational institution is certainly unavoidable because conflict is caused by many factors or circumstances. Conflict is not always bad, but it can also have a positive impact, as long as it is managed properly. This is where the madrasah principal is needed to manage conflict in a school he leads. The principal of course must make or prepare a strategy so that later problems that arise in the school can be controlled properly and optimally. This is in accordance with the duties and functions of the madrasa principal as a mediator, so that later the conflict does not become an obstacle for the madrasa to achieve its mission and goals.